Efficient Electrochemical Potentiostatic Activation Method for GaN-Based Green Vertical-LEDs. (17th March 2018) - Tawfik, Wael Z.; Cho, Sung Oh; Ha, Jun-Seok; Ryu, Sang-Wan; Cai, Duan-Jun; Lee, June Key
Abstract : An efficient electrochemical potentiostatic activation (EPA) method was designed and performed for hydrogen atoms removal from inside a Mg-doped gallium nitride (GaN) layer of green vertical light-emitting diodes (V-LEDs). The EPA method was conducted at the potentiostatic conditions of 2, 3, and 5 V for 5 mins. The role of the applied voltage value in the breaking of the Mg-H complexes and in increasing the holes concentration inside the p-GaN layer in terms of LED device performances was investigated. The internal quantum efficiency (IQE) of the green V-LEDs behaved inversely with the applied voltage. The IQE of green V-LEDs EPA processed with a low voltage of 2 V realized an improvement of about 6% and only about 2.5% for green V-LEDs EPA processed with a high voltage of 5 V at an injection current of 100 mA compared to the conventional rapid thermal annealing method. The light output power achieved the highest enhancement of about 10.5% at 100 mA when applying the lowest voltage of 2 V, which originated from an improvement of the IQE. The forward voltage was also reduced after the EPA process. The developed EPA method was proven to effectively improve the external quantum efficiency of green V-LEDs.